The Effects of Plasma-Activated Water Treatment on the Growth of Tartary Buckwheat Sprouts - Wang, Ya; Nie, Zihan; Ma, Tingjun (Frontiers in Nutrition, 2022)
The aim was to investigate the effects of buckwheat seeds sprout treated with plasma activated water (PAW) and their quality, nutrients (protein, amino acids, fat and carbohydrates), functional active ingredients (total flavonoids, total phenolic acids, γ-GABA and polysaccharides) and antioxidant activity during germination. PAW had no negative effects on germination rate, but promoted stem growth instead, which indicated 1.12-fold higher germination rate compared with CK group. The results of sensory evaluation demonstrated that the obtained sprouts were bright green, shinning, crisp and smooth, with sufficient moisture and easy to chew. During germination (1-9 d), the water content, amino acids, and reducing sugars of sprouts showed an increasing trend and were basically higher in the PAW group than in the CK group, while protein, carbohydrate, and crude fat presented a decreasing trend. The results were that the flavonoid, phenolic acid, γ-GABA, polysaccharide content and antioxidant activity during germination showed a gradual upward trend but with slight differences, and the antioxidant properties of buckwheat sprouts might be related to the phenolic acid and polysaccharide content. These data show that PAW treatment on buckwheat sprout have great potential as a dietary source of antioxidant function with health benefits.